Controllable wettability on stainless steel substrates with highly stable coatings. (23rd February 2019) - Su, Meng-Jun; Bai, Shun; Luo, Young; Chu, Guang-Wen; Sun, Bao-Chang; Le, Yuan; Chen, Jian-Feng
Highlights: Coatings with controllable wettability and high stability were fabricated. The micro-characteristics and macro-wettabilities of the coatings were studied. The structure-function relationship of the prepared coatings was revealed. Dynamic wettability and stability performances of modified-SSTs were tested. Abstract: A rotating packed bed (RPB) is one of the typical process intensification equipment and its performance can be influenced by the surface wettability of packings. However, tuning the surface wettability of the packing by the surface-modification method is still a challenge due to the extreme physical and chemical environment in RPBs. This work presents a facile strategy for controlling the surface wettability on the stainless steel substrate with a series of highly stable coatings. The water contact angles on the surfaces can be tuned from 75° to 160°. Based on the systematical analysis from the micro-characteristics (surface microstructure and surface free energy) to the macro-wettabilities (water contact angle) of the prepared coatings, the structure-function relationship of these coatings was revealed with wetting models. Application performance testing indicates that the coatings displayed strong adhesion, long-time corrosion resistance, and liquid impinging resistance under high-gravity conditions. This work opens a new avenue to produce highly stable coatings on stainless steel substrates with controllable wettability, which is very helpful to the wettability control for the stainless steel wire mesh packing of RPBs for industrial applications.